Investigating Teachers’ and Students’ Attitudes towards the Use of English as a Medium of Instruction in Higher Education in Algeria. The Case of Second-Year Students and Teachers of computer science faculty, University of M’sila - Chekhaba Amani.Bounab Chahinez, Dr. ABADOU Fadhila (université mohamed boudiaf .m'sila, 2023)
Abstract The study aims to investigate the attitudes of both teachers and students towards the use of English as a medium of instruction in the Faculty of Information Technology and Computer Science at M'sila University. Building upon previous works in this area, the study seeks to understand the perspectives and preferences regarding the use of English as a potential alternative to French within Algerian universities. To accomplish the research objectives. Quantitative and qualitative data were collected through the administration of two questionnaires, the first one was published online and seventy-five (75) second-year information technology and computer science students respond to it, the second questionnaire was handed out to 21 teachers who answered the questionnaire given to them along with an interview conducted with the head of the department. By utilizing this methodology, the study sought to capture a comprehensive understanding of the attitudes toward English as a medium of instruction. The findings of this study shed light on the participants' recognition of the importance of English as a medium of instruction in the Faculty of Information Technology and Computer Science. Notably, a majority of the participants exhibited positive attitudes toward the utilization of English in their academic pursuits. These findings contribute to the existing body of knowledge and offer valuable insights for learners, teachers, and policymakers. Through exploring the perspectives of both teachers and students, the study offers a deeper understanding of the potential pedagogical implications of implementing English as a medium of instruction in higher education in Algeria.
Keywords: Keywords: English as a medium of instruction, teachers’ attitudes, students’ attitudes, the head of the department, faculty of information technology and computer science.